Pocket Switched Networking: Challenges, Feasibility and Implementation Issues - Hui, Pan; Chaintreau, Augustin; Gass, Richard; Scott, James; Crowcroft, Jon; Diot, Christophe (Proceedings of the Second IFIP on Autonomic Communications 2005, 2005)
The Internet is built around the assumption of contemporaneous end-to-end connectivity. This is at odds with what typically happens in mobile networking, where mobile devices move between islands of connectivity, having opportunity to transmit packets through their wireless interface or simply carrying the data toward a connectivity island. We propose Pocket Switched Networking, a communication paradigm which reflects the reality faced by the mobile user. Pocket Networking falls under DTN. We describe the challenges that this approach entails and provide evidence that it is feasible with today's technology.